Lung Rest During Extracorporeal Membrane Oxygenation for Neonatal Respiratory Failure—Practice Variations and Outcomes. Issue 7 (July 2017) - Alapati, Deepthi; Aghai, Zubair H.; Hossain, Md Jobayer; Dirnberger, Daniel R.; Ogino, Mark T.; Shaffer, Thomas H.
Abstract : Objective: Describe practice variations in ventilator strategies used for lung rest during extracorporeal membrane oxygenation for respiratory failure in neonates, and assess the potential impact of various lung rest strategies on the duration of extracorporeal membrane oxygenation and the duration of mechanical ventilation after decannulation. Data Sources: Retrospective cohort analysis from the Extracorporeal Life Support Organization registry database during the years 2008–2013. Study Selection: All extracorporeal membrane oxygenation runs for infants less than or equal to 30 days of life for pulmonary reasons were included. Data Extraction: Ventilator type and ventilator settings used for lung rest at 24 hours after extracorporeal membrane oxygenation initiation were obtained. Data Synthesis: A total of 3, 040 cases met inclusion criteria. Conventional mechanical ventilation was used for lung rest in 88% of cases and high frequency ventilation was used in 12%. In the conventional mechanical ventilation group, 32% used positive end-expiratory pressure strategy of 4–6 cm H2 O (low), 22% used 7–9 cm H2 O (mid), and 43% used 10–12 cm H2 O (high). High frequency ventilation was associated with an increased mean (SEM) hours of extracorporeal membrane oxygenation (150.2 [0.05] vs 125 [0.02]; p < 0.001) and an increased mean (SEM) hours of mechanical ventilation after decannulation (135 [0.09] vs 100.2 [0.03]; p = 0.002), compared with conventional mechanical ventilation among survivors. Within the conventional mechanical ventilation group, use of higher positive end-expiratory pressure was associated with a decreased mean (SEM) hours of extracorporeal membrane oxygenation (high vs low: 136 [1.06] vs 156 [1.06], p = 0.001; mid vs low: 141 [1.06] vs 156 [1.06]; p = 0.04) but increased duration of mechanical ventilation after decannulation in the high positive end-expiratory pressure group compared with low positive end-expiratory pressure ( p = 0.04) among survivors. Conclusions: Wide practice variation exists with regard to ventilator settings used for lung rest during neonatal respiratory extracorporeal membrane oxygenation. Use of high frequency ventilation when compared with conventional mechanical ventilation and use of low positive end-expiratory pressure strategy when compared with mid positive end-expiratory pressure and high positive end-expiratory pressure strategy is associated with longer duration of extracorporeal membrane oxygenation. Further research to provide evidence to drive optimization of pulmonary management during neonatal respiratory extracorporeal membrane oxygenation is warranted.